Sensor sensitivity of nanocomposite and polymer thin films to ammonia vapors in air - Salikhov Р.; Ostaltsova А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2023)
The article is devoted to the study of nanocomposite thin films based on a polyelectrolyte complex of chitosan and chitosan succinamide (PEC), single-walled carbon nanotubes (SWCNT) and polyaniline derivatives were used as fillers. Using a scanning electron microscope, the morphology of the surface of thin films obtained from a solution of synthesized polymers by centrifugation on citall substrates was studied. Studying the nature of morphology is extremely important when creating sensory devices. Based on these polymers, samples of resistive thin-film structures were prepared, and the dependence of their electrical conductivity on the current passing through the sample was measured when the concentration of ammonia vapors changed. A study of the surface of the nanocomposite structure of PEC with SWCNT using SEM showed that there are filamentous formations formed by carbon nanotubes on it.